Field checklist of Iowa birds contributed by Randall Pinkston, September 26, 1991 - Pinkston, Randallet al (1991)
List of birds and locations contributed by Randall Pinkston with observers James L. Fuller, Charles Fuller and James Scheib. The field notes include detailed information on three Merlin sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed